2019
DOI: 10.1159/000502832
|View full text |Cite
|
Sign up to set email alerts
|

A Clinico-Radiological Study of Cerebral Amyloid Angiopathy-Related Inflammation

Abstract: Objective: To describe the clinico-radiological features and long-term prognosis in patients with cerebral amyloid angiopathy-related inflammation (CAA-ri). Methods: Twenty-eight CAA-ri patients were recruited retrospectively from 6 neurological centers. We recorded the clinico-radiological and biological data, at baseline and during follow-up. Baseline characteristics associated with relapse risk and prognosis were assessed. Results: Five patients had pathologically confirmed CAA-ri whereas 23 had probable (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
3
20
1
1
Order By: Relevance
“…Headache and seizure are often shown 12 . Visual symptoms were also seen 12 . Our nationwide survey based on 16 cases of CAA‐ri showed that dementia and headache were the most frequently observed as initial manifestations 6 .…”
Section: Clinical Manifestations Of Caamentioning
confidence: 85%
See 3 more Smart Citations
“…Headache and seizure are often shown 12 . Visual symptoms were also seen 12 . Our nationwide survey based on 16 cases of CAA‐ri showed that dementia and headache were the most frequently observed as initial manifestations 6 .…”
Section: Clinical Manifestations Of Caamentioning
confidence: 85%
“…In patients with CAA‐ri, the most frequent manifestations are acute or subacute‐onset cognitive impairment and behavioral changes 10,11 . Headache and seizure are often shown 12 . Visual symptoms were also seen 12 .…”
Section: Clinical Manifestations Of Caamentioning
confidence: 99%
See 2 more Smart Citations
“…Despite an apparently favorable initial evolution after a prompt empirical immunosuppressive therapy [24] , CAA-ri is characterized by a poor prognosis attributed to different factors such as CAA-relapses, intracerebral hemorrhages (ICH) and infectious or vascular complications [25] , [26] .…”
Section: Introductionmentioning
confidence: 99%